Faktor - Faktor Yang Mempengaruhi Produksi Usahatani Ubi Kayu Di Desa Mataram Udik Kecamatan Bandar Mataram - Armawan, Nyoman; Sutarni, Sutarni; Noer, Irmayani; Fitriani, Fitriani (CV. ITTC INDONESIA, 2023)
Cassava is the third largest consumption food in Indonesia after rice and wheat, which is 6.78% per capita per year. One of the commodities cultivated in Mataram Udik Village is cassava. Increased income and production of cassava will be achieved if fertilization is optimal. The purpose of this research is to analyze the factors that influence production and to analyze the income of cassava farming in Mataram Udik Village, Bandar Mataram District. This research was conducted from July to August 2022. Sampling was carried out by simple random sampling and the number of respondents was 43 cassava farmers. Data analysis in this study used multiple regression analysis with the production function of the Cobb-Douglas equation and income analysis. Based on the results of the study it can be seen that the factors that influence cassava production at a significant level of 5% are land area (X1), seeds (X2), chemical fertilizers (X3), labor (X5) and dummy organic fertilizers (D1). While the production factors that have no significant effect on cassava production are herbicides (X4), because the probability value is more than the 5% significance value - the average income for cassava farming is Rp. 95,407,121/2.47 ha and Rp. 38,632,085/ha in one growing season. The average total cost of cassava farming is Rp. 32,598,717/2.47 ha and Rp. 13,197,861/ha. The average income of cassava farmers is Rp. 62,808,404/2.47 ha and Rp. 25,428,504/ha in one growing season. In cassava farming, an R/C ratio of 2.92 and a B/C ratio of 1.92 means that every Rp. 1 spent will generate revenue of Rp. 2.92. This R/C ratio explains that cassava farming is feasible and the B/C value is greater than 1 which means cassava farming is profitable and can be increased.